The Role of Omega-3 in Improving Clinical Symptoms of Children With Urinary Tract Infections: A Randomized Clinical Trial: Omega-3 in Children With Urinary Tract Infections - Toghra, Arshia; Kahbazi, Manijeh; Arjmand Shabestari, Ali; Yousefichaijan, Parsa; Mohaghegh, Pegah; Toghra, Alireza (Journal of Pediatric Nephrology, 2026)
Background and Aim: Inflammatory urinary tract infection (UTI) is a common infectious disease in childhood, causing significant discomfort. Omega-3 fatty acids are well-known for their anti-inflammatory properties, which may aid in decreasing UTI symptoms. This study aimed to investigate the effects of omega-3 therapy in children with UTI. Methods: This randomized clinical trial enrolled 100 children with UTIs, randomized into placebo and intervention groups. In addition to standard treatment, the intervention group received one omega-3 capsule daily. Symptoms were assessed at the baseline and again after the treatment period. Results: At baseline, no significant differences were observed between the two groups in age, gender, or symptom prevalence. However, after the treatment period, omega-3 supplementation resulted in a significant decrease in dysuria and urinary frequency symptoms compared to the placebo group. Conclusion: Omega-3 supplementation as adjunct therapy can significantly improve the severity of symptoms in children with UTIs.